ISOLATION AND STRUCTUREELUCIDATIONSOF RESVERATROLOLiGOMERS FROM STEM BARK OF Dryobalanops lanceolata Isolasl dan Penentuan Struktur Oligomer Resveratrol darl Kullt Batang Dryobalanops lanceolata - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Five resveratrol oligomers which consist of two resveratrol dimers, balanocarpol (1) and e-viniferin (2), a resveratrol trimer i.e. a-viniferin (3), and two resveratrol tetramers, vaticanol B (4), and hopeaphenol (5) have been isolated from acetone extract of the stem bark of Dryobalanops lanceolata. These compounds were isolated by vacuum liquid chromatography method. Furthermore, the compound structures were determined based on the spectroscopic evidence, including UV, IR, 1-0 and 20 NMRspectra, and comparing with those related data reported previously. . Keywords: Balanocarpol,e-Viniferin,a-Viniferin, VaticanolB, Hopeaphenol,D. lanceolata